RESULTS OF »EUROHEART FAILURE« SURVEY IN SLOVENIA: CHARACTERISTICS AND DIAGNOSTIC PROCEDURES IN HOSPITALISED HEART FAILURE PATIENTS - Mitja Lainščak; Mateja Kerbev; Alojz Horvat; Davorin Benko; Maja Klančnik Gruden; Irena Keber (Zdravniški Vestnik, 2004)
Background. In years 2000–1 European Society of Cardiology performed an »EuroHeart Failure« Survey in 24 European countries, including Slovenia. The aim of the survey was to determine the characteristics, diagnostic and therapeutic management of patients, hospitalised for heart failure. Methods. In the prospective survey medical records of all patients admitted during six weeks of April and May 2000 to the University Medical Centre, Internal Medicine Clinic, and Internal medicine departments of General Hospitals Murska Sobota and Slovenj Gradec were screened. Only patients with diagnosis of heart failure on discharge or death were included. Results. Out of 1351 screened we included 358 patients (52% males), aged 73 ± 12 years. Hospitalization index was first hospitalization for heart failure in 41% of patients. On admission, 84% of patients presented with signs of heart failure, 68% were in New York Heart Association class III, and 28% in class IV. Myocardial infarction was recorded in 22%, angina pectoris in 34%, arterial hypertension in 46%, Diabetes mellitus in 34%, respiratory disease in 34%, and renal failure in 28% of patients. During hospitalization (11.6 ± 8.1 days), 11% of patients died and during 12 weeks after discharge additional 7% of them. 26% of patients were rehospitalized in twelve weeks after discharge. Almost all patients had electrocardiogram, chest X-ray and results of basic laboratory tests (full blood count, electrolytes, creatinine). Echocardiography report was found in 57% of patients. Systolic dysfunction was present in 70% of investigations. Conclusions. Heart failure is very common in internal medicine patients. Short term prognosis is gloomy with frequent rehospitalizations. Coronary disease and arterial hypertension are major aetiologies of heart failure, accompanied by many  comorbidities. Echocardiography is still not accepted as standard method in diagnostic assessment of heart failure.